2020
DOI: 10.5582/ddt.2020.03112
|View full text |Cite
|
Sign up to set email alerts
|

5-Aminolevulinic acid combined with sodium ferrous citrate (5-ALA/SFC) ameliorated liver injury in a murine acute graft-versus-host disease model by reducing inflammation responses through PGC1-α activation

Abstract: Acute graft-versus-host disease (aGvHD) remains lethal as a life-threatening complication after allogeneic hematopoietic stem cell transplantation (HSCT). Inflammatory responses play an important role in aGvHD. 5-Aminolevulinic acid combined with sodium ferrous citrate (5-ALA/SFC) has been widely reported to have a major effect on the anti-inflammatory response; however, these effects in aGvHD models have never been reported. In this study, a murine aGvHD model was developed by transferring spleen cells from d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…It accomplishes these multifaceted effects by linking itself to a variety of proteins that regulate cellular metabolism, such as peroxisome proliferator-activated receptors (PPARs), nuclear respiratory factor-1/2, farnesoid X receptor, liver X receptor, forkhead box protein O1 (FOXO1), sirtuin 1 (Sirt1), tumor protein p53 and hepatocyte nuclear factor 4. Wang et al showed that increasing PGC-1α mRNA expression stimulates mitochondrial activity and ameliorates liver injury by increasing the IL-10-mediated anti-inflammatory response [161]. Further studies revealed that PGC-1αmediated mitochondrial biogenesis plays a vital role in mitigating the high-fat diet-induced hepatic steatosis development [162].…”
Section: Role Of Pgc-1α On Inflammatory Responsementioning
confidence: 99%
“…It accomplishes these multifaceted effects by linking itself to a variety of proteins that regulate cellular metabolism, such as peroxisome proliferator-activated receptors (PPARs), nuclear respiratory factor-1/2, farnesoid X receptor, liver X receptor, forkhead box protein O1 (FOXO1), sirtuin 1 (Sirt1), tumor protein p53 and hepatocyte nuclear factor 4. Wang et al showed that increasing PGC-1α mRNA expression stimulates mitochondrial activity and ameliorates liver injury by increasing the IL-10-mediated anti-inflammatory response [161]. Further studies revealed that PGC-1αmediated mitochondrial biogenesis plays a vital role in mitigating the high-fat diet-induced hepatic steatosis development [162].…”
Section: Role Of Pgc-1α On Inflammatory Responsementioning
confidence: 99%